MiR-940 potentially promotes proliferation and metastasis of endometrial carcinoma through regulation of MRVI1. Issue 6 (10th June 2019) - Zhou, Zhan; Xu, Ya-Ping; Wang, Li-Juan; Kong, Yan
Abstract : The specific functions and clinical significance of miR-940 in endometrial carcinoma (EC) have not been studied. First, we assessed the expression of miR-940 and MRVI1 in EC tissues collected from The Cancer Genome Atlas (TCGA) database and EC cell lines. miR-940 was significantly overexpressed in EC tissues and cell lines, particularly in RL95-2 cells. Correlation analysis showed that miR-940 expression level was remarkably associated with age, grade, and death. Moreover, the overall survival (OS) rate in the miR-940 low expression group was higher, compared with miR-940 high expression group. Univariate and multivariate models demonstrated that miR-940 expression, stage, and age were predictive indicators of OS. Moreover, there was no significance of the proliferation ability among the three EC cell lines (RL95-2, ISK, and KLE). To reveal the biological roles of miR-940, we respectively transfected RL95-2 cells with miR-940 mimics, miR-940 inhibitors, and control to further investigate the cell proliferation ability, and migration as well as invasion potential of RL95-2 cells. The transfection of miR-940 mimics significantly increased the proliferation and migration/invasion ability of RL95-2 cells. MRVI1 was predicted to be a potential target of miR-940 by means of in silico analysis followed by validation using luciferase reporter assays. MRVI1 was correlated with good prognosis. Moreover, forced expression of MRVI1 in miR-940 mimic transfected cells abolished the facilitation of miR-940 on cell proliferation, migration, and invasion of RL95-2 and KLE cells. In conclusion, our study demonstrates that miR-940 might function as a reliable diagnostic and prognostic signature in EC.